Konsep Dasar Pendidikan Islam: Landasan Filosofis dan Praktis dalam Pembentukan Karakter Islami - M. Zelfen Syahrifal; Aldio habib aswari; Gusmaneli (CV. ITTC INDONESIA, 2024)
This research addresses the critical issues surrounding the role of Islamic education in character development among youth in the context of globalization. The primary objective of this study is to explore how Islamic education can effectively instill moral values and ethical behavior in students, enabling them to navigate the challenges posed by modern society. A qualitative approach was employed, utilizing interviews and surveys with educators, students, and parents to gather insights on the impact of Islamic education on character formation. The findings indicate that Islamic education significantly contributes to the development of integrity, social awareness, and environmental consciousness among students. Furthermore, it highlights the necessity of integrating Islamic values into the educational curriculum to foster a generation that is not only academically proficient but also morally upright and socially responsible.